Visual Branding of Warkop Kandang Ayam: Constructing an Aesthetic Social Space Image on Instagram - Mohammad Farhat Abel; Vilya Dwi Agustini; Hendri Prasetya (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study analyzes Warkop Kandang Ayam's visual branding strategy in building an aesthetic social space image through Instagram. In the digital media era, visual communication plays a crucial role in shaping brand identity, audience perception, and social interactions in online spaces. Instagram is not only utilized as a promotional platform, but also as a medium for constructing social meaning and visual experiences. This study uses a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, non-participant observation, and documentation of Instagram content, including feeds, Reels, captions, and audience interactions. The findings show that Warkop Kandang Ayam consistently applies a warm visual feel, natural photography style, spatial composition, and communicative digital narratives to create a comfortable and aesthetic brand image. Audience interactions through comments, likes, and shares also strengthen the construction of brand identity in the digital communication space. These findings support the theory of Computer-Mediated Communication, particularly the concept of selective self-presentation in building a digital identity through curated visual communication. This study contributes to communication and media studies by explaining how Instagram-based visual branding can transform a local coffee shop into an aesthetic social space in contemporary digital culture. Keywords: Aesthetic social space, Visual branding, Computer-Mediated Communication, Digital communication, Instagram.